Are all labor regulations equal? Evidence from Indian manufacturing - Ahmad Ahsan; Carmen Pagés (Institute for the Study of Labor (IZA), 2008)
Using manufacturing data for India, this paper studies the economic effects of legal amendments on two types of labor laws: employment protection and labor dispute resolution legislation. We find that laws that increase employment protection or the cost of labor disputes substantially reduce registered sector employment and output. These laws do no seem to benefit workers either, as they do not increase the share of value added that goes to labor. Labor-intensive industries, such as textiles, are the hardest hit by amendments that increase employment protection while capital-intensive industries are the most affected by laws that increase the cost of labor dispute resolution. These adverse effects are not alleviated by the widespread and increasing use of contract labor, particularly in regards to employment. Results are robust to an alternative codification of legal amendments suggested by Bhattacharjea (2006).
Keywords: J23; 330; Employment protection; labor dispute resolution; contract labor; employment; India; Arbeitsrecht; Kündigungsschutz; Schlichtung; Beschäftigungseffekt; Indien